2022
DOI: 10.1093/infdis/jiac260
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the HIV Vaccine Trials Network 702 Phase 2b–3 HIV-1 Vaccine Trial in South Africa Assessing RV144 Antibody and T-Cell Correlates of HIV-1 Acquisition Risk

Abstract: Background The ALVAC/gp120 + MF59 vaccines in the HVTN 702 efficacy trial did not prevent HIV-1 acquisition. Vaccine-matched immunological endpoints that were correlates of HIV-1 acquisition risk in RV144 were measured in HVTN 702 and evaluated as correlates of HIV-1 acquisition. Methods Among 1893 HVTN 702 female vaccinees, 60 HIV-1-seropositive cases and 60 matched seronegative non-cases were sampled. HIV-specific CD4+ T-ce… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 38 publications
0
20
0
Order By: Relevance
“…Nevertheless, the only HIV vaccine clinical trial demonstrating modestly efficacious is "The RV144 Thai trial", with 31.2% protection 7 . However, the efficacy of the clinical trial of "The HVTN-702", conducted as an extension of the RV144 trial 8,9 , was ineffective 10,11 . Further, recently the clinical efficacy trials of the "Imbokodo study" (HVTN 705/HPX2008) and "the Mosaico" (HVTN 706/ HPX3002 Mosaico) were pre-maturely discontinued due to the lack of efficacies 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the only HIV vaccine clinical trial demonstrating modestly efficacious is "The RV144 Thai trial", with 31.2% protection 7 . However, the efficacy of the clinical trial of "The HVTN-702", conducted as an extension of the RV144 trial 8,9 , was ineffective 10,11 . Further, recently the clinical efficacy trials of the "Imbokodo study" (HVTN 705/HPX2008) and "the Mosaico" (HVTN 706/ HPX3002 Mosaico) were pre-maturely discontinued due to the lack of efficacies 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Squalene is easily metabolized by the body, and numerous studies have shown that squalene-based oil-in-water nano adjuvants can induce both good humoral and cellular immune responses [ 41–43 ]. Moreover, the squalene adjuvant MF59 has been approved for influenza vaccines [ 44 ]. Therefore, we used AddaVax adjuvant, similar in composition to MF59, to evaluate the immunogenicity of inactivated rS-MARV.…”
Section: Resultsmentioning
confidence: 99%
“…HIV is still a major problem in the world and particularly in South Africa, where it is estimated that 7.9 million people are living with HIV—which translates to 14% of the population [ 1 ]. One of the means of controlling the ongoing HIV pandemic is by prophylactic vaccination; unfortunately, only one trial has shown modest efficacy [ 2 ] with a number of recent vaccine trials being unsuccessful [ 3 , 4 ]. Trials of infused monoclonal antibodies demonstrated the broadly neutralizing monoclonal antibody, VRC01, was able to prevent infection by viruses that were sensitive to neutralization by this antibody [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the RV144 trial, the correlate of protection was described as high V1V2 Ab reactivity in plasma and low Env-specific IgA in plasma [ 16 ]. However, clinical trials based on the same concept as RV144 have not been successful [ 3 ]. In addition, while a lot of emphasis is placed on testing HIV vaccines in non-human primates, the correlates of protection that have been predicted from non-human primate studies as well as various clinical trials are not consistent [ 17 ].…”
Section: Introductionmentioning
confidence: 99%